Making Sense of Pain: Participatory Design Approaches to Understanding and Supporting People Living with Chronic Pain - Nakarada-Kordic, Ivana; Seck, Jannisa; Beetge, Nathan; Khoo, Cassandra; Reay, Stephen (Design Research Society, 2026)
Pain is universal, yet its invisible nature makes it difficult to express or understand. Understanding the intricate mechanics of chronic pain and how to manage it effectively can be particularly challenging. This paper describes research exploring how human-centred design, transdisciplinary collaboration, and participatory approaches can produce diverse design outcomes that support the management and treatment of chronic pain. Two case studies are presented: 1) an exploration of how pain might be expressed through illustration and storytelling to offer insight into lived experience, and 2) how experiences of pain could be made more tangible through physical artefacts to support patient–clinician communication. The resulting design outcomes – an illustrated resource for patients and a tangible toolkit for use in therapeutic settings – present novel alternatives to existing communication tools. The involvement of both learned experts and those with lived experience ensured these outcomes were relevant, usable, and implementable in real-world contexts.
Keywords: 32 Biomedical and Clinical Sciences; 33 Built Environment and Design; 3202 Clinical Sciences; 3209 Neurosciences; 3303 Design; Pain Research; Neurodegenerative; Neurosciences; Chronic Pain; Peripheral Neuropathy; 7.1 Individual care needs; Generic health relevance; Neurological; Musculoskeletal